Characterization of a satellite DNA in the genera Lacerta and Timon (Reptilia, Lacertidae) and its role in the differentiation of the W chromosome. Issue 2 (9th February 2018) - Giovannotti, Massimo; Nisi Cerioni, Paola; Rojo, Verónica; Olmo, Ettore; Slimani, Tahar; Splendiani, Andrea; Caputo Barucchi, Vincenzo
Abstract: In this study, IMO‐TaqI satDNA, previously isolated in several species of Lacertidae, was isolated and characterized from four species of the genus Lacerta and three of the genus Timon . The aim was to gain further insights into the evolutionary dynamics of this satDNA, its occurrence among lacertids and to understand if it plays any role in sex chromosome evolution in these seven species. The results here obtained highlighted the presence of this repetitive element in the genome of all the species investigated, thus indicating that IMO‐TaqI satDNA is evolutionary conserved among a wide variety of lacertids. In addition, this element was found to be very abundant in the constitutive heterochromatin of the W‐sex chromosome of the four Lacerta species investigated. The occurrence of IMO‐TaqI satDNA on Lacerta heterochromosome suggests that it is involved in the differentiation of the W chromosome by heterochromatinization, and the fact that it is absent in the W of other lacertids investigated seems to confirm that repetitive DNA sequences would remain randomly trapped into the sex chromosomes, undergoing amplification as a consequence of the suppression of recombination. GRAPHICAL ABSTRACT: In this study, IMO‐TaqI satDNA, previously isolated in several species of Lacertidae, was isolated and characterized from four species of the genus Lacerta and three of the genus Timon . The results here obtained highlighted the presence of this repetitive element in the genome of all the species investigated, thus indicating that IMO‐TaqI satDNA is evolutionary conserved among a wide variety of lacertids. In addition, this element was found to be very abundant in the constitutive heterochromatin of the W‐sex chromosome of the four Lacerta species investigated. The occurrence of IMO‐TaqI satDNA on Lacerta heterochromosome suggests that it is involved in the differentiation of the W chromosome by heterochromatinisation. FISH with IMO‐TaqI probe onto metaphases from females of: Timon lepidus (A), Lacerta agilis (B), L. trilineata (C), L. strigata (D). A species‐specific probe was used for each species. The arrow indicates the W chromosome. Scale bar =10 μm.